Transfer of training: does it truly happen?: An examination of support, instrumentality, retention and learner readiness on the transfer motivation and transfer of training - Bhatti, Muhammad Awais; Battour, Mohamed Mohamed; Sundram, Veera Pandiyan Kaliani; Othman, Akmal Aini (Emerald Group Publishing Limited, 2013)
Purpose– The purpose of this study is to highlight the importance of selected environmental, situational and individual factors in the training transfer process. Design/methodology/approach– This study proposes and tests a framework via structural equation modelling by including supervisor and peer support, instrumentality and learner readiness on 503 Malaysian bank employees. It proposes a modified and improved scale for learner readiness previously developed by Holton et al..Findings– As hypothesized, supervisor and peer support increase the motivation level of the trainee to transfer the learned skills.The findings of this study will help researchers to resolve the conflict among past researchers about the role of peer and supervisor support in training transfer process.In addition, an improved scale of learner readiness is used and the result indicates a significant relationship between learner readiness and transfer motivation. Furthermore, this study explains the importance of intrinsic rewards and finds that intrinsic rewards make trainees retain more skills and learned skills are transferred to the work place.Practical implications– The findings of this research would be helpful for human resource development professionals to develop effective strategies in order to maximize the training transfer and effectively manage the training program.The findings of this research explained the role of stakeholders – trainers, trainees, supervisors, peers and top management – which will maximize the training transfer at the work place.Originality/value– This paper examines new relationships among different factors which resist transfer motivation and training transfer at the workplace.